هيئة نيابة الأموال العامة ودورها في تحقيق الاستقرار الاجتماعي في الجمهورية اليمنية: دراسة فقهية تحليلية - فقير,علي صالح علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research addresses the role of public funds prosecution in achieving social stability in Yemen. The study seeks to address two research questions: how can the concept of protection of public funds be defined?, what are the terms of reference and the constraints of public funds institutes?, Based on this, a mixed method (consisting the quantitative and qualitative approaches) was used, whereby 115 questionnaires were distributed to Yemeni academicians, businessmen, and administrators who have a good understanding of this issue. Then, five staff members from the public funds prosecution were interviewed in order to investigate the obstacles they face. The samples for both of the questionnaire and the interview were selected using purposive sampling. In the same vein, the concept of public funds in Islamic jurisprudence is explained along with the means of protecting it. This explanation is supported by the religious scholars' ('Ulama) explanation and definitions of public funds. In addition, the researcher explains the supervisory organizations for the public funds in Islam as well as the means of protecting it and its role in ensuring social stability. Furthermore, the researcher explains the role of social stability in economic policy, including economic revival and sustainable development. Moreover, the researcher discusses the concept of social stability in the Holy Qur'an and Sunnah as well as Islamic jurisprudence. The researcher also explores the concept of prosecution for public funds and its social responsibility as well as the possible obstacles that impede its role in this regard. The findings equally indicate that there are a number of constraints represented in legislative and regulatory obstacles as well as influence-peddling. Accordingly, the research concludes with some recommendations which enable the public funds prosecution to perform a better role in the social stability in Yemen.